2001
DOI: 10.1126/science.294.5545.1354
|View full text |Cite
|
Sign up to set email alerts
|

CNS Synaptogenesis Promoted by Glia-Derived Cholesterol

Abstract: The molecular mechanisms controlling synaptogenesis in the central nervous system (CNS) are poorly understood. Previous reports showed that a glia-derived factor strongly promotes synapse development in cultures of purified CNS neurons. Here, we identify this factor as cholesterol complexed to apolipoprotein E-containing lipoproteins. CNS neurons produce enough cholesterol to survive and grow, but the formation of numerous mature synapses demands additional amounts that must be provided by glia. Thus, the avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
1,140
2
16

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,480 publications
(1,217 citation statements)
references
References 29 publications
38
1,140
2
16
Order By: Relevance
“…Higher neuron densities that we observed in association with added astroglia are likely to result from this decreased excitotoxicity and from trophic factors that are released by astroglia and promote neuronal survival. Mauch et al (2001) showed that cholesterol produced by astroglia added to cultures of retinal ganglion neurons contributes to an increased quantal content, a higher density of synapsin puncta, an increased EPSC frequency and a decrease failure rate at synapses. Thrombospondin, an extracellular matrix protein, is another neurotrophic factor released by astroglia that promotes synaptogenesis (Christopherson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Higher neuron densities that we observed in association with added astroglia are likely to result from this decreased excitotoxicity and from trophic factors that are released by astroglia and promote neuronal survival. Mauch et al (2001) showed that cholesterol produced by astroglia added to cultures of retinal ganglion neurons contributes to an increased quantal content, a higher density of synapsin puncta, an increased EPSC frequency and a decrease failure rate at synapses. Thrombospondin, an extracellular matrix protein, is another neurotrophic factor released by astroglia that promotes synaptogenesis (Christopherson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes also increase the number of functional synapses on CNS neurons sevenfold, and are required for maintenance of synapses in vitro (Ullian et al, 2001). Further experiments show that cholesterol derived from CNS glia is sufficient to facilitate synapse formation (Mauch et al, 2001). These studies suggest that glia may dynamically regulate synapse number.…”
Section: Glia-another Source Of Extrinsic Regulatory Signalsmentioning
confidence: 99%
“…It is a major structural component of plasma membranes and myelin, where it is critical for rapid conduction of nerve transmission. Cholesterol has also been directly implicated in various neuronal functions, including synaptogenesis and neurotransmitter release (Mauch et al, 2001 andThiele et al, 2000). Indirectly it has a general influence on cerebral biochemistry via conversion into bioactive steroids such as neurosteroids and oxysterols.…”
Section: Introductionmentioning
confidence: 99%